Polymeric Nanocapsules Containing Fennel Essential Oil: Their Preparation, Physicochemical Characterization, Stability over Time and in Simulated Gastrointestinal Conditions - Giuseppe Granata; Carla Riccobene; Edoardo Napoli; Corrada Geraci (MDPI AG, 2022)
Plant essential oils, a source of biologically active compounds, represent a promising segment in the pharmaceutical market. However, their volatility, hydrophobicity, poor stability, and low toxicity limit direct use in pharmaceutical-related applications. Nanoencapsulation is a technique that allows overcoming these obstacles by improving bioaccessibility and bioavailability. Nanocapsules (NCs) based on biodegradable and biocompatible poly(ɛ-caprolactone) containing Foeniculum vulgare Mill. essential oil (FEO), known for its biological activities, were successfully prepared by interfacial deposition of the preformed polymer method. The composition of FEO (trans-anethole chemotype) was determined by gas chromatography analyses. The FEO presence inside the NCs was confirmed by nuclear magnetic resonance experiments. The FEO-NCs showed nanometer size (210 nm), low polydispersity index (0.10), negative zeta potential (−15 mV), non-Newtonian rheological behavior, and high efficiency of encapsulation (93%). Moreover, parameters such as FEO-NC particle size, bioactive compound retention, and FEO composition were monitored for 30 days at storage temperatures of 4 and 40 °C, confirming the robustness of the nanosystem. Finally, FEO-NCs were resistant to the simulated gastric digestion and showed an effective bioaccessibility of 29% in simulated intestinal digestion. Based on the results obtained, this FEO-NC nanosystem could find interesting applications in the nutraceutical and pharmaceutical sectors.